The Use of Health Education Media to Improve Knowledge and Treatment Adherence among Tuberculosis Patients at the Pringsewu Community Health Center, Lampung - Dinda Annisa; Iga Mayola Pisacha; Mida Pratiwi; Sulistia Suryaman (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2026)
Tuberculosis (TB) remains a serious public health problem. Low levels of knowledge and non-adherence to treatment are major factors contributing to treatment failure and an increased risk of drug resistance. This study aims to analyze the effect of education on the knowledge and adherence of tuberculosis patients. A pre-experimental study design with a one-group pre-test and post-test design was used, employing total sampling of 35 patients. Data were collected using a validated TB knowledge questionnaire and the MMAS-8, and analyzed using the Wilcoxon Signed-Rank Test. The results showed an increase in the average knowledge score from 75 to 83, with the good category rising from 54.3% to 74.3%. Adherence increased from 6.82 (moderate) to 7.55 (high), with the high category rising from 42.9% to 57.1%. The Wilcoxon test yielded a p-value of 0.002 for knowledge and p = 0.017 for adherence (p < 0.05). It was concluded that education using Microsoft PowerPoint and leaflets had a significant effect on improving knowledge and treatment adherence among tuberculosis patients.